Association of reduced glutathione levels with Plasmodium falciparum and Plasmodium vivax malaria: a systematic review and meta-analysis - Manas Kotepui; Kwuntida Kotepui; Aongart Mahittikorn; Hideyuki J. Majima; Jitbanjong Tangpong; Hsiu-Chuan Yen (Scientific Reports, 2023)
Abstract Reduced glutathione (GSH) is a crucial antioxidant with recognized roles in malaria pathogenesis and host response. Despite its importance, reports on the association of GSH with malaria are inconsistent. Therefore, this systematic review and meta-analysis investigated the differences in GSH levels in relation to Plasmodium infection. A comprehensive literature search of six electronic databases (Embase, MEDLINE, Ovid, PubMed, Scopus, and ProQuest) was conducted. Of the 2158 initially identified records, 18 met the eligibility criteria. The majority of studies reported a significant decrease in GSH levels in malaria patients compared with uninfected controls, and this was confirmed by meta-analysis (P < 0.01, Hedges g: − 1.47, 95% confidence interval [CI] − 2.48 to − 0.46, I 2 : 99.12%, 17 studies). Additionally, there was no significant difference in GSH levels between Plasmodium falciparum malaria and P. vivax malaria (P = 0.80, Hedges g:  0.11, 95% CI − 0.76 to 0.98, I 2 : 93.23%, three studies). Similarly, no significant variation was observed between symptomatic and asymptomatic malaria cases (P = 0.78, Hedges g: 0.06, 95% CI − 0.34 to 0.46, I 2 : 48.07%, two studies). In conclusion, although GSH levels appear to be generally lower in malaria patients, further detailed studies are necessary to fully elucidate this complex relationship.